Nickel-enhanced electrochemical activities of shape-tailored TiO2001 nanocrystals for water treatment: A combined experimental and DFT studies. (20th April 2021) - Shao, Cairu; Lin, Litian; Duan, Lijuan; Jiang, Yusi; Shao, Qingyi; Cao, Hongyang
Abstract: Understanding the reaction mechanism at the solid/liquid interface is necessary to improve the catalytic activity of electrode materials for water treatment. In this study, the photoelectrocatalytic degradation of rhodamine B (RhB) and phenol in water was studied using undoped and Ni-doped TiO2 with 001 facets (TiO2 001). Under visible light irradiation, Ni-doped TiO2 electrodes exhibited higher contamination removal efficiency than undoped ones. Photoluminescence detection and density functional theory calculations revealed that the Ni-doped TiO2 provides a better hydroxyl radical yield and adsorption capacity than the undoped TiO2, which could be a major reason for the improvement of the catalytic activity of Ni-doped TiO2 . The diffuse reflectance spectroscopy data showed that introducing the Ni 2+ ions into TiO2 can shift the absorption edge towards the visible light region, which also contributes to the excellent photoelectrocatalytic performance. This work provides a strategy for improving the electrochemical performance of TiO2 and an in-depth understanding of the doping and catalytic mechanism of Ni 2+ ions. Graphical abstract: Image, graphical abstract